UPDATES ON THE TREATMENT OF OBSTRUCTIVE LOWER URINARY TRACT DISEASE IN CATS - Cipriano, Luanda Ferreira; Flores, Rafael Sartori; Barros, Camille Moreira Bergamo; Medeiros, Dreyd Rodrigues; Martins, Carolina Aires; Saraiva, Gabriela Victoria Araújo; Teixeira, Barbara Fernandes Werneck; Tinoco, Isis Alexandra Pincella; Luvison, Nicole Amoêdo; Afolabi, Oladapo Olawale; Mendonça, Ana Paula Abreu (Seven Editora, 2025)
Feline lower urinary tract diseases affect about 15 to 57% of cats, being one of the most important causes of cat visits to the veterinarian. Pandora's syndrome affects cats with lower urinary tract diseases (FLUTD), resulting in dysuria, hematuria, periuria, frequency, and stranguria. Most clinical cases of cats that present these alterations are considered as "clinically unexplained syndromes" or idiopathic, and may be related to genetic factors and epigenetic influences. Cat obstructive lower urinary tract disease can be potentially fatal because it involves a water, electrolyte and acid-base imbalance and acute kidney injury. Treatment options include clinical treatment, surgery, and changes in environmental management and behavior adaptation of cats. Clinical treatment, in many cases, is ineffective, penectomy and perineal urethrostomy surgeries are effective surgical techniques for clearing urinary flow in felines, more frequent in males, but they are associated with high rates of postoperative death (8%-22%).  Through the use of the implantation of a subcutaneous ureteral device, the urine passes through an artificial system, surgically placed, preserving the animal's ureter that is not viable. The use of this device is associated with good long-term results and a lower lethality rate. To date, no official guidelines are available in veterinary medicine to assist veterinarians in making decisions about the best treatment for these diseases, however the placement of a ureteral device remains the standard treatment of choice and is associated with the highest success rates, in addition to medications to minimize stress and management changes.DOI: https://doi.org/10.56238/sevened2024.037-140